Rediscovery of Ipomoea salsettensis (Convolvulaceae) from Western Ghats of Maharashtra, India - Kattee, A.V.; Borude, D. B.; Chandore, A. N.; Patil, C. R.; Shimpale, V. B. (Rheedea, 2017)
Ipomoea salsettensis Santapau & Patel (Convolvulaceae) is rediscovered from the Western Ghats of Maharashtra, after a lapse of 58 years. A detailed taxonomic description, illustration, photographs and relevant notes are provided.